L’enseignement des expressions idiomatiques en première année licence de FLE - Nabila Tatah (Multilinguales)
Idiomatic expressions and fixed expressions are main part of the language. They are derived from literature and belong to the sociocultural heritage. When speaking of teaching it seems interesting to involve the learners by including those expressions in the written domain. According to Laurent Perrin (2002). "The meaning of these constructions, which are sometimes called ready-made or idiomatic, like that of most words in the language, is based on a previously established conceptual representation, which must have been previously memorised in order to be fully understood. " Learning and using these expressions thus empowers the learner by looking at another way of communicating.